Letter from Marianne Homburger to Max Bredig, December 7, 1938 - Homburger, Marianne (1938)
Marianne Homburger (1903-1987) explains to her brother, Max Bredig (1902-1977), which documents and financial assets would be necessary for her and her family to emigrate to England while they await a visa for the United States. The final page of this letter is missing.
Keywords: Homburger, Marianne, 1903-1986; Bredig, Max Albert, 1902-1977; Emigration and immigration; Jewish Holocaust (1939-1945); Third Reich